The influence of novel organic gold complex on photoresist layers of printed circuit boards - Silvana Dimitrijević (Metallurgical & Materials Engineering, 2015)
The goal of this paper was to study the influence of organic gold complex based on mercaptotriazole on photoresist layers used in manufacturing of printed circuit boards (PCBs). Investigations were performed by immersion the previously prepared boards in electrolytes with different pH values (pH=2, 4, 7, 9 and 12) at gold concentration of 2.5 g/dm3 and in gold complexes with different gold concentrations (1.5; 2.0; 2.5; 3.0 and 3.5 g/dm3) at pH value of pH=9. Investigations showed that photoresist layers on boards are the most resistant at optimal operating conditions, pH=9 and concentration of gold of 2.5 g/dm3.